Review on the Effect of the Phenomenon of Cavitation in Combustion Efficiency and the Role of Biofuels as a Solution against Cavitation - Ludovic Lamoot; Brady Manescau; Khaled Chetehouna; Nicolas Gascoin (Energies, 2021)
Concerning the problem of wanting the performance of heat engines used in the automotive, aeronautics, and aerospace industries, researchers and engineers are working on various possibilities for improving combustion efficiency, including the reduction of gases such as CO, NOx, and SOx. Such improvements would also help reduce greenhouse gases. For this, research and development has focused on one factor that has a significant impact on the performance of these engines: the phenomenon of cavitation. In fact, most high-performance heat engines are fitted with a high-speed fuel supply system. These high speeds lead to the formation of the phenomenon of cavitation generating instabilities in the flow and subsequently causing disturbances in the combustion process and in the efficiency of the engine. In this review article, it is a question of making a state-of-the-art review on the various studies which have dealt with the characterization of the phenomenon of cavitation and addressing the possible means that can be put in place to reduce its effects. The bibliographic study was carried out based on five editors who are very involved in this theme. From the census carried out, it has been shown that there are many works which deal with the means of optimization that must be implemented in order to fight against the phenomenon of cavitation. Among these solutions, there is the optimization of the geometry of the injector in which the fuel flows and there is the type of fuel used. Indeed, it is shown that the use of a biofuel, which, by its higher viscosity, decreases the effects of cavitation. Most of these jobs are performed under cold fluidic conditions; however, there is little or no work that directly addresses the effect of cavitation on the combustion process. Consequently, this review article highlights the importance of carrying out research work, with the objective of characterizing the effect of cavitation on the combustion process and the need to use a biofuel as an inhibitor solution on the cavitation phenomenon and as a means of energy transition.